Exploration of Natural Media in Contextual Learning for the Development of Early Childhood Numeracy Skills - Ariyanti, Agus; Zulkarnaen, Z (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
Purpose: This research is motivated by the need to develop numeracy skills in early childhood meaningfully through the use of natural media as a contextual learning tool.Methodology: The goal of this study is to outline the methodology and findings of investigating the use of natural media in numeracy instruction for kids in the 4–5 age range at Aisyiyah Bustanul Athfal Depok II Kindergarten. The method used is a descriptive qualitative approach with data collection through participatory observation, in-depth interviews, and documentation, then analyzed interactively and descriptively quantitatively to see the achievement of child development indicators.Results: The results show that the use of natural media consistently has a positive impact with an average achievement of 89.3% in the numeracy aspect, high child involvement, and very positive teacher perceptions. These results show that natural media is a useful medium for learning numeracy and corroborate Piaget's theory of cognitive development and the concepts of contextual learning. The practical implication is that teachers are advised to integrate natural materials into lesson plans and act as active facilitators.Applications/Originality/Value This research has limitations in sample size and observation period, so it is recommended that ongoing research with an experimental design and broader scope is recommended. Overall, this study confirms the importance of exploring natural media as an effective and relevant numeracy learning strategy in early childhood education.